Biochanin A Attenuates Ovariectomy-Induced Cognition Deficit via Antioxidant Effects in Female Rats - Zhou, Yanmeng; Xu, Bingbing; Yu, Haiyang; Zhao, Wei; Song, Xinxin; Liu, Yan; Wang, Kainan; Peacher, Nikoli; Zhao, Xiaomin; Zhang, Han-Ting (Frontiers in Pharmacology, 2021)
Background: Impairment of memory and cognition is one of the major symptoms in women with postmenopausal disorders due to estrogen deficiency, which accounts for the much higher prevalence of Alzheimer’s disease in females. Biochanin A (BCA), a natural phytoestrogen, has been reported to protect neurons against ischemic brain injury. However, the neuroprotective effects of BCA in the postmenopausal-like model of ovariectomized (OVX) rats remain to be investigated. Methods: All the rats except for the sham group underwent the resection of bilateral ovaries. Seven days after the OVX surgery, rats were randomly divided into six groups: sham, OVX, OVX+BCA (5 mg/kg), OVX+BCA (20 mg/kg), OVX+BCA (60 mg/kg), and OVX+ estradiol (E2; 0.35 mg/kg), which were administrated daily by gavage for 12 weeks. Learning and memory were examined using the Morris water-maze test before the end of the experiment. Morphological changes of the rat hippocampus were observed by HE staining and electron microscopy. Malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) in the hippocampus were measured. The effect of BCA on cell viability was measured in the presence of hydrogen peroxide (H2O2) using CCK8. Flow cytometry was used to measure neuronal apoptosis and reactive oxygen species (ROS) induced by H2O2. Expression of Bcl-2, Bax, and Caspase-3 was determined by Western blotting using hippocampus and primary cultures of hippocampal neurons. Results: Chronic treatment with BCA mimicked the ability of E2 to reverse the deficit of learning and memory in the Morris water-maze test in OVX rats. BCA normalized OVX-induced morphological changes as revealed by HE staining and electron microscopy. In addition, BCA significantly decreased the levels of MDA, the biomarker of oxidative damage, and increased the activity of the intracellular antioxidant enzymes SOD and GSH-Px in OVX rats. Further, in primary cultures of hippocampal neurons, BCA reversed H2O2-induced decreases in cell viability and accumulation of ROS. Finally, BCA reversed OVX- or H2O2-induced increases in Bax and Caspase-3 and decreases in Bcl-2 . Conclusions: BCA improves memory through its neuroprotective properties in the brain under the circumstance of estrogen deficiency and can be used for treatment of memory loss in postmenopausal women.